Ab initio spillover compensation in mass cytometry data. Issue 9 (31st December 2020) - Miao, Qi; Wang, Fang; Dou, Jinzhuang; Iqbal, Ramiz; Muftuoglu, Muharrem; Basar, Rafet; Li, Li; Rezvani, Katy; Chen, Ken
Abstract: Signal intensity measured in a mass cytometry (CyTOF) channel can often be affected by the neighboring channels due to technological limitations. Such signal artifacts are known as spillover effects and can substantially limit the accuracy of cell population clustering. Current approaches reduce these effects by using additional beads for normalization purposes known as single‐stained controls. While effective in compensating for spillover effects, incorporating single‐stained controls can be costly and require customized panel design. This is especially evident when executing large‐scale immune profiling studies. We present a novel statistical method, named CytoSpill that independently quantifies and compensates the spillover effects in CyTOF data without requiring the use of single‐stained controls. Our method utilizes knowledge‐guided modeling and statistical techniques, such as finite mixture modeling and sequential quadratic programming, to achieve optimal error correction. We evaluated our method using five publicly available CyTOF datasets obtained from human peripheral blood mononuclear cells (PBMCs), C57BL/6J mouse bone marrow, healthy human bone marrow, chronic lymphocytic leukemia patient, and healthy human cord blood samples. In the PBMCs with known ground truth, our method achieved comparable results to experiments that incorporated single‐stained controls. In datasets without ground‐truth, our method not only reduced spillover on likely affected markers, but also led to the discovery of potentially novel subpopulations expressing functionally meaningful, cluster‐specific markers. CytoSpill (developed in R) will greatly enhance the execution of large‐scale cellular profiling of tumor immune microenvironment, development of novel immunotherapy, and the discovery of immune‐specific biomarkers. The implementation of our method can be found at https://github.com/KChen-lab/CytoSpill.git .